Carbon-based raw materials play key roles in technology of the 21st century: Indian case studies (Rudarsko-geološko-naftni zbornik, 2022)
Coal is a vital carbon-based raw material which is used in the production of various advanced nanomaterials. This particularly holds true for the relevant research and development trends in India. New more environmentally friendly processes are under development with respect to metallurgical coke making and quality enhancement of high-ash Indian coal. Compared with chemical and physical methods, beneficiation of high-ash coal and its combustion by-products with organic liquids (various natural oils) are much more superior in terms of costs, efficiency, and environmental implications. Nanodiamonds have emerged as a key platform for nanoscience and nanotechnology developments. Indian scientists have applied eco-friendly and cost-effective ultrasonic assisted wet-chemical method to low-quality NE Indian coal and the resulting nanodiamond particles could have a wide range of applications in the field of microelectronics, optoelectronics, and biosensing. Also, Indian scientists have been working on ultrasonic-assisted chemical synthesis of activated carbon from low-quality subbituminous coal and its preliminary evaluation towards supercapacitor applications. This article shows that coal is a versatile and valuable raw material which should be saved for future generations at all costs.